The bianchetto truffle (Tuber borchii) a lead‐resistant ectomycorrhizal fungus increases Quercus cerris phytoremediation potential. (18th November 2022) - Sisti, Davide; Donati Zeppa, Sabrina; Amicucci, Antonella; Vittori Antisari, Livia; Vianello, Gilmo; Puliga, Federico; Leonardi, Pamela; Iotti, Mirco; Zambonelli, Alessandra
Abstract: Tuber borchii is a European edible truffle which forms ectomycorrhizas with several soft‐ and hardwood plants. In this article, the effects of high level of Pb on the in vitro growth of five T . borchii strains and the molecular mechanisms involved in Pb tolerance were studied. Moreover, the effects of the Pb treatment on T . borchii ectomycorrhizas and on the growth, element uptake and distribution in different organs of Quercus cerris seedlings were investigated. The results showed an extraordinary tolerance of T . borchii mycelium to Pb: all the tested strains were able to grow at Pb concentration over 4000 mg L −1 . The mechanisms of tolerance seem related to Pb sequestration in the vacuole and its immobilization as crystal of Pb oxalate outside the hyphae rather than detoxification processes, considering the low expression of glutaredoxin and thioredoxin genes. T . borchii–Q . cerris mycorrhizas tolerate a soil concentration of Pb from 1869 to 4030 mg kg −1 although, at these Pb concentrations, T . borchii showed a reduced ability to colonize roots. T . borchii mycorrhization increased the uptake of Pb by Q . cerris . Mycorrhization and Pb treatment also significantly influenced the uptake and translocation in the plant of other elements.